Physical, Mental and Sexual Health Among Transgender Women: A Comparative Study Among Operated Transgender and Cisgender Women in a National Tertiary Referral Network. Issue 5 (23rd March 2021) - Vedovo, Francesca; Di Blas, Lisa; Aretusi, Francesco; Falcone, Marco; Perin, Chiara; Pavan, Nicola; Rizzo, Michele; Morelli, Girolamo; Cocci, Andrea; Polito, Chiara; Gentile, Giorgio; Colombo, Fulvio; et al.
ABSTRACT: Background: Few studies have investigated how physical, mental and sexual function are associated with each other in operated transgender women (oTW). Aim: To provide information on the physical, mental and sexual health of oTW in comparison with a group of cisgender women (cisW). Methods: An age-matched control study was carried out, recruiting 125 oTW in 7 national referral centers and 80 volunteer women. Beck Depression Inventory Primary Care (BDI-PC), General Health Survey (SF-36), Female Sexual Function Index (FSFI) and operated Male to Female Sexual Function Index (oMtFSI) questionnaires were web-based administered. Data included: age, area of origin, educational level, sexual orientation, years since surgery and hormone therapy. Outcomes: T-test was applied to inspect mean score differences between oTW and cisW, in mental, sexual and physical health; simple correlations and multiple regression analysis revealed how mental, sexual and physical health were concurrently associated in the two groups RESULTS: Response rate 60% (52% oTW, 71% cisW). oTW mean age 38.5 years (SD = 9.3), cisW 37.7 years (SD = 11.5). Both cisW and oTW reported average values in the range of mental, physical and sexual health. Statistical comparisons revealed no significant group differences in mental and physical health. oTW who referred a worse sexual function also reported worse overall mental well-being and higher levels of depressive symptoms. FSFI scores were negatively associated with years since surgery, but not with age. Multiple regression analysis showed that FSFI Pain accounted for a significant unique variance proportion of risk of depression in oTW. FSFI Sexual Pain was the strongest estimator of inter-individual differences in BDI-PC among oTW ( P < .01). Clinical Implications: No significant differences in the levels of depressive symptoms, physical and mental well- being were found in oTW and cis-W. The relation between depressive symptoms and sexual function in oTW is stronger than in cisW, and sexual pain substantially predicts risk of depression in oTW. Strengths & Limitations: The evaluation of outcomes using validated questionnaires and the relatively large sample size. The convenience control group reported mental, physical and sexual health levels within the range of Italian normative data. Since this is a cross-sectional study, we must be careful in drawing conclusions from our results. CONCLUSIONS: Sexual pain and lubrication difficulties are the main causes of worse sexual function in oTW, highlighting the importance of perioperative counseling to make surgical expectations realistic and to educate to a proper neovagina management.